The Position of the Vienna Convention on the Law of Treaties of 1969 on the Problem of the Provisional Application of an International Treaty - Bediar, Derradji (Journal of Legal Studies and Researches, 2024)
This study deals question of the implementation of international treaties from the aspect of their temporary application, its purpose achieving compatibility between the national procedures, and at the same time trying to accelerate the implementation of the texts of the international treaty, and the Vienna Convention 1969 is tried to achieve compatibility.